Bim and vr: development of a software module for the integration of building information modelling and virtual reality - T. A. Kozlenko; S. V. Pridvizhkin (Вестник СибАДИ)
Introduction. Based on the trends, the growing interest in VR technology in construction can be traced. This relatively new technology is rapidly replacing traditional visualization methods, providing users with an enhanced digital experience. The aim of the work is to analyze the application of virtual reality technology in construction, based on the analysis, determine how to improve integration and find new ideas for the application of technologies.Methods and materials. As a result of the analysis of previous studies, it was revealed that there are no methods for transferring data from the VR system to the BIM software. In connection with the identified problem, the goal of this scientific work is to improve the integration of VR and BIM technologies by automatically transferring data from a virtual reality program to the original information model.Results. In the course of the work, a project was created based on a BIM model made in the Autodesk Revit software package and imported into the Unreal Engine 4 game engine to create an interactive virtual environment. A new approach to the creation and presentation of a project sketch using virtual reality technology is considered - a method of intuitive design in a virtual environment.Discussion and conclusion. The software module is at the stage of early development; nevertheless, it has prospects for development into a full-fledged application available to any user. The paper provides the main directions for the continuation of the application development.